PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH BIOLOGI UMUM PROGRAM STUDI PENDIDIKAN BIOLOGI UNIVERSITAS CENDERAWASIH (The Impact of Learning Style towards StudentsÃ¢â¬â¢ Study Achievement on the Subject of General Biology, of Biolog - Tanta, Tanta (KREATIF, 2010)
In designing learning strategy, a lecturer should pay attention to input characteristics, such as studentsÃ¢â¬â¢ learning style, motivation, and other factors. Therefore, it is important for a lecturer to know his teaching style so that there is no gap between lecturer and his students. Students should also know their learning style in order to choose the most effective learning method for them. The objective of this research was to know the impact of studentsÃ¢â¬â¢ learning style towards their study achievement on the subject of general biology. Population of the research were that all the students of semester IÃÂ 2009/2010 of biology education program, and total of the samples were 31 students. Instruments used to gathering the data were observation, questionnaire, and documentation. It used SPSS to analyze the data. The research result showed that studentsÃ¢â¬â¢ learning style belonged to visual type. Learning style was influential to studentsÃ¢â¬â¢ study achievement on statictic p-value 0.000 (ÃÂ < 0.05) and t statistic value for independent variable was 8.850 on concrete degree 5%. Type of the regression was Y = 18,292 + 0,892X. The result of statistical validation test F showed the p-value 0.000 ( < 0.05) and determination coefficient or R square was 0.73, and it meant that 73% of the studentsÃ¢â¬â¢ study result were influenced by their learning style. Keyword: learning style, and study achievement.